Penguins - Barkhausen, Annette; Geiser, Franz (Milwaukee : Gareth Stevens Pub., 1994)
An introduction to members of the penguin family, including chinstrap penguins, Fiordland penguins, and Macaroni penguins.
Orginally published: Lucerne, Switzerland : Kinderbuchverlag KBV Luzern AG, 1992.
Includes bibliographical references (p. 47) and index.
Keywords: Penguins -- Juvenile literature; Penguins